THE ROLE OF GREEN ROOFS IN URBAN SUSTAINABILITY - Someh, Mina Farokhi; Basiri, Mostafa; Azim, Ali Zeynali (European Scientific Journal, ESJ, 2014)
Dynamic urban processes and constant evolutions in the types of living as well as technological advances have changed and manipulated living environments for human beings. The increasing growth in the population of urban regions and the escalation of socioeconomic problems have forced human beings to live in matchbox apartments during the last a few decades. Modern human beings have to encounter different daily activities to make living; hence, having a shelter which can bring peace and relief has become a dream for him. Recent urban views and sights have been changed into apartments and tall towers in the residential areas which have made human habitats gloomy and bleak and have created several problems for modern citizens. It can be argued that, regardless of the internal peace of houses, urban citizens need beautiful and green natural views and sceneries far from the tensions of work environments so as to comfort their minds and imaginations. Projects for modernizing, optimizing and creating new urban spaces are realized in different areas for many years. The present study is intended to examine the concept and idea of green garden which has been proposed by developed countries. The concept of green garden was proposes as an attempt to fulfill tranquility, peace and a desirable habitat. The present study investigated and evaluated this proposition based on the following criteria: compatibility, desirability, efficiency, comfort, safety and health.